2016
DOI: 10.1002/cssc.201601249
|View full text |Cite
|
Sign up to set email alerts
|

Graphite//LiNi0.5Mn1.5O4 Cells Based on Environmentally Friendly Made‐in‐Water Electrodes

Abstract: The performance of graphite//LiNi Mn O (LNMO) cells, both electrodes of which are made using water-soluble sodium carboxymethyl cellulose (CMC) binder, is reported for the first time. The full cell performed outstandingly over 400 cycles in the conventional electrolyte ethylene carbonate/dimethyl carbonate-1 m LiPF , and the delivered specific energy at the 100th, 200th, 300th, and 400th cycle corresponded to 82, 78, 73, and 66 %, respectively, of the initial energy value of 259 Wh kg (referring to the sum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…The specific energy (based on the anode and cathode active material) is 312 Wh kg −1 for the 3 rd cycle, accompanied by an energy efficiency of remarkable 86 %. Such specific energy is superior to a comparable graphite/LNMO full‐cell with 259 Wh kg −1 , while the energy efficiency is slightly lower compared to the latter system (above 90 %) – though in the same range as for lithium‐ion full‐cells comprising a silicon/carbon composite as anode and LNMO as cathode . Upon cycling, however, the energy efficiency decreases to 74 % in the 50 th cycle, which is in line with the moderate increase in voltage hysteresis observed in Figure b for the anode.…”
Section: Resultsmentioning
confidence: 99%
“…The specific energy (based on the anode and cathode active material) is 312 Wh kg −1 for the 3 rd cycle, accompanied by an energy efficiency of remarkable 86 %. Such specific energy is superior to a comparable graphite/LNMO full‐cell with 259 Wh kg −1 , while the energy efficiency is slightly lower compared to the latter system (above 90 %) – though in the same range as for lithium‐ion full‐cells comprising a silicon/carbon composite as anode and LNMO as cathode . Upon cycling, however, the energy efficiency decreases to 74 % in the 50 th cycle, which is in line with the moderate increase in voltage hysteresis observed in Figure b for the anode.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, simply substituting the conventional binder, PVDF, with CMC results in the improved structural integrity of NCM upon cycling. These results are in line with a previously published study comparing the performance of LNMO electrodes made with CMC and PVDF binders, which showed that the former binder can actually protect the active material particles [293].…”
Section: Resultssupporting
confidence: 93%
“…It is revealed that fading mechanisms of the high‐voltage LiNi 0.5 Mn 1.5 O 4 /graphite full cell are special and complicated, and the dominate “disease” is “hemopathy,” which originates from the decomposition of “blood” (conventional LiPF 6 ‐based carbonate electrolytes), the subsequent Mn/Ni dissolution–migration–deposition and serious loss of active lithium (especially at graphite electrode) . Diversified strategies, such as LiNi 0.5 Mn 1.5 O 4 material modification (coating and doping), electrolyte optimization (new lithium salts, solvents, and functional additives), new cathode binder development, etc., have been proposed to enhance the performances of LiNi 0.5 Mn 1.5 O 4 /graphite full cells. One of the most economical, feasible, and effective remedial strategy is prescribing a small amount of “medicine” (functional additive) for “blood” to modify and stabilize the solid–electrolyte interface (SEI) layer, which greatly influences the electrochemical performances and safety of LIBs …”
Section: Introductionmentioning
confidence: 99%